Mechanical, thermal and biodegradable properties of polylactic acid (PLA)/coir fibre biocomposites - Dong, Yu; Ghataura, Arvinder; Haroosh, Hazim (Society of Photo-Optical Instrumentation Engineers (SPIE), 2013)
Polylactic acid (PLA)/coir fibre biocomposites were fabricated using a compression moulding technique. The effects of fibre content (5-30 wt%) and fibre treatment on mechanical, thermal and biodegradable properties of biocomposites were holistically investigated via mechanical testing, scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and soil burial method to understand the applicability of manufacturing eco-efficient and sustainable “green composites”.